Banate Bay mangrove reforestation program prospective ares for community-based property rights (CBPRs) - Ungkakay, Farisal B (Miagao, Iloilo University of the Philippines Visayas, 2004)
The study focuses on the Mangroves Reforestation Program of the Banate Bay Resource Management Council, Inc. (BBRMCI), particularly in the 5 coastal barangays bordering Banate Bay, Iloilo, namely: Tiwi, Palaciauan, Pantalan, Belen and Takokgangan. It describes the processes, issues and prospects encountered by BBRMCI in the implementation of the mangrove reforestation project. Focus group discussion with key informants at the community, as well as interview of BBRMCI staff done to capture the initiatives and mechanisms involved in the program, organizational arrangements in these areas and the issues the BBRMCI faces in the program implementation. It further explores the feasibility of transferring the management of such initiative to the local communities or communal groups in the area. A set of criteria was used to assess the capacity of existing organizations to assume management responsibilities for the mangrove resources. These are: presence of clearly defined boundaries for the resources, presence of a small user's group with mutual obligations and rules aginst defectors, an overlap between the location of the common property and organization or community member's residence, degree of dependence of the user group on the resource and support from local decision-makers. Although results shows that most of the above mentioned criteria are present in the Barangay Fisheries and Aquatic Resources Management Councils (BFARMCs), conditions at the community level still, are not conducive for the transfer of management responsibilities to BFARMCs primarily because BFARMCs areconsidered as government-arms and not independent groups. Second, there is a need to define the level of importance of each of the 5 criteria to achieve the desired success of CBPRs. Other equally important features are therefore recommended, in addition to the criteria used, to increase the chances of success of the Mangrove Reforestation Program of BBRMCI. These are: (1) defining the user group' s capacity: (2) system of sanctions and rewards within and outside a user group; and (3) presence of appropriate legal institutions that will allow wxclusive use rights over the resources to qualified user groups.
Special Problem (MMA) -- Miagao, Iloilo : U.P. Visayas, 2004.
Keywords: Mangrove reforestation program -- Banate Bay